Abusive Head Trauma in Children: A Literature Review - Nahara R.L. Lopes; Evelyn Eisenstein; Lúcia C.A. Williams (Brazilian Society of Pediatrics, 2013)
Objective: : To review the scientific literature on pediatric abusive head trauma as a form of physical abuse against infants and young children, highlighting the prevalence, signs and symptoms, consequences, risk factors for its occurrence, and prevention strategies. Data source: : The MEDLINE, SciELO, LILACS, and Web of Science databases from 2001 to 2012 were reviewed, using the terms "shaken baby syndrome" and "abusive head trauma" in English, Spanish, and Portuguese. Data synthesis: : Pediatric abusive head trauma is defined as injury to the skull or intracranial contents of a infant or child younger than 5 years due to intentional abrupt impact and/or violent shaking. It occurs mainly in infants and children under 1 year of age, and may result in severe consequences, from physical or mental disabilities to death. Although there are specific signs for this form of abuse, they can be mistaken for common illnesses in children or accidental head injury; thus, clinical training of professionals involved in the assessment of cases to attain the correct diagnosis is crucial. Prevention strategies should include early identification of cases, as well as parental education on child development, especially on the infant's crying pattern. Conclusions: : Considering the severity of abusive head trauma in children, it is critical that prevention strategies be implemented and evaluated in the Brazilian context. It is suggested that its incidence indicators be assessed at the national level.